CVD Synthesis of MoS2 Using a Direct MoO2 Precursor: A Study on the Effects of Growth Temperature on Precursor Diffusion and Morphology Evolutions - Ratchanok Somphonsane; Tinna Chiawchan; Waraporn Bootsa-ard; Harihara Ramamoorthy (My University, 2023)
In this study, the influence of growth temperature variation on the synthesis of MoS2 using a direct MoO2 precursor was investigated. The research showed that the growth temperature had a strong impact on the resulting morphologies. Below 650 °C, no nucleation or growth of MoS2 occurred. The optimal growth temperature for producing continuous MoS2 films without intermediate-state formation was approximately 760 °C. However, when the growth temperatures exceeded 800 °C, a transition from pure MoS2 to predominantly intermediate states was observed. This was attributed to enhanced diffusion of the precursor at higher temperatures, which reduced the local S:Mo ratio. The diffusion equation was analyzed, showing how the diffusion coefficient, diffusion length, and concentration gradients varied with temperature, consistent with the experimental observations. This study also investigated the impact of increasing the MoO2 precursor amount, resulting in the formation of multilayer MoS2 domains at the outermost growth zones. These findings provide valuable insights into the growth criteria for the effective synthesis of clean and large-area MoS2, thereby facilitating its application in semiconductors and related industries.
Keywords: Morphology; 2D Materials and Applications